On the commutator of Marcinkiewicz integrals with rough kernels in variable Morrey type spaces - Qu, M.; Wang, L. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5 In the framework of variable exponent Morrey and Morrey–Herz spaces, we prove some boundedness results for the commutator of Marcinkiewicz integrals with rough kernels. The approach is based on the theory of variable exponent and on generalization of the BMO-norms.